Ovimbundu identity attributions in post-war Angola - Martins, V. (2016)
This article explores the attribution of political identity to the Ovimbundu ethnic group of Angola during the post-war period. It examines specific historical periods and political debates to reveal negative stereotypes popularly used to associate this ethnic group with the Unia˜o Nacional para a Independeˆncia Total de Angola (UNITA), a practice still present today. Academic scholarship concerning the ethnic debate about Angola is still embryonic. This paper negotiates a new approach by looking at ethnic stereotypes as enduring means of attributing political identity to a specific ethnic group, while taking into account the views of those targeted by such identity attributions. Having explored how UNITA mobilised the Ovimbundu for political gains, the paper uses interview data collected in the central highlands to demonstrate not only the attribution of stereotypes but also the Ovimbundu’s own perception of themselves as a ‘marginal other’. It is in the group’s interaction with wider Angolan society that such stereotypes are summoned and shaped in the pejorative epithets ‘bailundo’, ‘kwacha’ and ‘sulano’. The article concludes that decades of ethnic manipulation provided various identity connotations, based on ethno-regional and socio-political criteria. These were often contrary to actual Ovimbundu outlooks, but still served as limiting factors to their social, political and economic integration. Thus the Ovimbundu’s own perception of their marginalisation has been reinforced.